Documentation storage: integrated documents management (IDM ) at Integrated Logistics Berhad - Warehouse No. 6 Subang Jaya / Al Azmi Abdul Rahman - Abdul Rahman, Al Azmi (1996)
Continuous planning and constant improvements are the key factors of a successful company with efficient operation system. The efficiency of operation system is one of the elements that is of crucial importance to the company besides producing quality service. This research attempts to find out the effective process flow and proposed to the company namely, Integrated Warehouse Sdn. Bhd. no. 6. Furthermore, the researcher try to seek out problems in the process of documentation storage during observation and give recommendations to solve the problems. In this research, analysis are made on two types of process, that are Boxes For Collection and Storage, and Boxes For Viewing.